Provision of Innovative Learning Development and Assessment for Teachers at SDIT Al Multazam, Kuningan District - Ghullam Hamdu; Ade Yulianto; Agnestasia Ramadhani Putri; Anggit Merliana (ABDIMAS: Jurnal Pengabdian Masyarakat, 2023)
In supporting the increase in teacher capacity and competency, there is a need for continuous guidance for teachers through assistance from universities in the form of coaching and training. One of the training patterns must target how teachers can develop learning tools and authentic assessments appropriately and effectively in the learning process. The training carried out is introduction and technical guidance on the development of learning tools and authentic assessments. Teachers must have knowledge not only of subject matter but how that subject matter can be taught and learned as well as a more general knowledge of teaching and learning. The results of this activity are the teacher's initial understanding of the importance of implementing assessments in learning in elementary schools and producing teacher skills in developing authentic learning tools and assessments in education. Therefore, this activity will be relevant to be able to foster and assist in increasing teacher competence in pedagogy and professionalism within a certain time.